Potensi Ekstrak Biji Pala (Myristica fragrans L) Terhadap Penyembuhan Luka Bakar pada Mencit (Mus musculus) - Widy Susanti Abdulkadir; Endah Nurrohwinta Djuwarno; Zulkarnain Marhaba; Dizky Ramadani Putri Papeo (State University of Gorontalo, 2023)
The Nutmeg Plant (Myristica Fragrans L) is one of the spices plants empirically used as a therapeutic option for injury healing. Burn injury is damage to the skin's integrity caused by contact with a source with a high-temperature difference. This research aimed to determine the effectiveness of Nutmeg (Myristica Fragrans L) Seed extract on burn injury healing in Male Mice (Mus Musculus). Extraction was carried out through Maceration with Methanol solvent. Eighteen mice were divided into 6 groups: negative control (Na-CMC), positive control (Bioplacenton), and treatment groups with concentrations of 3%, 5%, 7%, and 10%. Burn injury was created using a 2 cm x 2 cm iron plate on the mice's back, and the healing of the burn injury diameter was observed from day 1 to day 20, with observation intervals at day 5, 10, 15, and 20. The data were analyzed using one-way ANOVA followed by an LSD test to determine the differences between test groups. The resalts indicate that the ethanol extract of Nutmeg (Myristica Fragrans L) see haseng effect on burn injury, with the most effective concentration being the extraet onoration of 10%, with a burn injury healing rate of up to 89,15%.